Analisis Pengaruh dan Dampak Inflasi, Suku Bunga dan Nilai Tukar Terhadap Realisasi Ekspor Batik di Indonesia dalam Perspektif Ekonomi Islam Tahun 2010-2023 - Yulianti, Ade Yeny; Pratomo, Dimas; Supriyaningsih, Okta (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the effect of inflation, interest rates, and exchange rates on the realization of Indonesian batik exports during the period 2010-2023 by considering an Islamic economic perspective. The research method used is a quantitative approach with the Vector Autoregressive (VAR) model. Data analysis includes stationarity test using the Augmented Dickey-Fuller (ADF) method, cointegration test to see the long-term relationship between variables, and estimation of the Vector Error Correction Model (VECM) model if a cointegration relationship is found. In addition, Impulse Response Function (IRF) and Variance Decomposition (FEVD) analysis are used to understand the response and contribution of each variable to batik exports. The results show that in the long run, inflation and exchange rates have a negative and significant effect on batik exports, while interest rates have a positive effect. IRF analysis reveals that batik exports take about seven months to return to equilibrium after experiencing an external shock. FEVD shows that inflation has the largest contribution in affecting batik exports compared to other variables. In conclusion, macroeconomic factors such as inflation, interest rates, and exchange rates have an important role in determining the performance of Indonesian batik exports. By considering the perspective of Islamic economics, stable and welfare-based policies can be proposed to improve the competitiveness of batik exports in the global market.